(untitled) (Baghdad Science Journal, 2021)
In this paper, the theoretical cross section in pre-equilibrium nuclear reaction has been studied for the reaction at energy 22.4 MeV. Ericson’s formula of partial level density PLD and their corrections (William’s correction and spin correction) have been substituted in the theoretical cross section and compared with the experimental data for nucleus. It has been found that the theoretical cross section with one-component PLD from Ericson’s formula when doesn’t agree with the experimental value and when . There is little agreement only at the high value of energy range with the experimental cross section. The theoretical cross section that depends on the one-component William’s formula and on-component corrected to spin PLD formula doesn’t agree with the experimental cross section. But in case of theoretical cross section based on two-component Ericson’s and William’s PLD formulae it has been found that there is acceptable agreement when the exciton number is taken .